A collaborative dynamic scenario model for the interaction of critical infrastructures. (November 2016) - Turoff, Murray; Bañuls, Victor A.; Plotnick, Linda; Hiltz, Starr Roxanne; Ramírez de la Huerga, Miguel
Highlights: We present a model of the cascading effects of Critical Infrastructure failures during disasters. We demonstrate how to deal with conflicting views when we have people with different backgrounds to develop a single model exhibiting their collective viewpoints. We show how such collaborative modeling exercises can provide for both planning and training of others in the potential consequences of mitigation of expected disasters. This research might be used as a reference in different contexts and by different groups for supporting emergency plans and risk analysis. Abstract: This paper reviews current work on a model of the cascading effects of Critical Infrastructure failures during disasters. Based upon the contributions of 26 professionals, we have created a reliable model for the interaction among sixteen Critical Infrastructures. An internal Critical Infrastructure model can be used as a core part of a number of larger models, each of which is tailored to a specific disaster in a specific location. We have shown that this collaborative modeling methodology is able to allow a group of professionals in Emergency Management to develop a single model exhibiting their collective viewpoints on interactions of Critical Infrastructure conditions. We demonstrate how to deal with conflicting views when we have people with different backgrounds and geographic origins. This research might be used as a reference in different contexts and by different groups for supporting emergency plans and risk analysis. This is especially necessary in this field because in critical infrastructures management, planning is required to include communications with other facilities that could be affected.